Just Ella - Haddix, Margaret Peterson (New York Aladdin Paperbacks, 2001)
In this continuation of the Cinderella story, fifteen-year-old Ella finds that accepting Prince Charming's proposal ensnares her in a suffocating tangle of palace rules and royal etiquette, so she plots to escape.
81219
Keywords: Princesses -- Juvenile fiction; Sex role -- Juvenile fiction